Prognostic value of galectin-3, a novel marker of fibrosis, in patients with chronic heart failure: data from the DEAL-HF study - Lok, Dirk J. A. (Springer-Verlag, 2010)
AIMS: Biomarkers are increasingly being used in the management of patients with chronic heart failure (HF). Galectin-3 is a recently developed biomarker associated with fibrosis and inflammation, and it may play a role in cardiac remodeling in HF. We determined its prognostic value in patients with chronic HF. METHODS AND RESULTS: Patients with chronic HF (New York Heart Association functional class III or IV) who participated in the Deventer–Alkmaar heart failure study were studied. Galectin-3 levels were determined at baseline using a novel optimized enzyme-linked immunosorbent assay. Univariate and multivariate analyses were used to determine the prognostic value of this biomarker. We studied 232 patients; their mean age was 71 ± 10 years, 72% were male, and 96% were in NYHA class III. During a follow-up period of 6.5 years, 98 patients died. Galectin-3 was a significant predictor of mortality risk after adjustment for age and sex, and severity of HF and renal dysfunction, as assessed by NT-proBNP and estimated glomerular filtration rate, respectively (hazard ratio per standard deviation 1.24, 95% CI 1.03–1.50, P = 0.026). CONCLUSION: Plasma galectin-3 is a novel prognostic marker in patients with chronic HF. Its prognostic value is independent of severity of HF, as assessed by NT-proBNP levels, and it may potentially be used in the management of such patients.